2013
DOI: 10.1038/ncomms3373
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact on direct neuronal reprogramming in vivo in the adult brain

Abstract: Direct reprogramming of non-neuronal cells to generate new neurons is a promising approach to repair damaged brains. Impact of the in vivo environment on neuronal reprogramming, however, is poorly understood. Here we show that regional differences and injury conditions have significant influence on the efficacy of reprogramming and subsequent survival of newly generated neurons in the adult rodent brain. A combination of local exposure to growth factors and retrovirus-mediated overexpression of the neurogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
238
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(246 citation statements)
references
References 60 publications
4
238
1
3
Order By: Relevance
“…For examples, postnatal astrocytes of the mouse cerebral cortex can be converted into glutamatergic and GABAergic neurons after overexpression of the transcription factors Neurog2 and Dlx2, respectively (Berninger et al, 2007b;. Several studies further showed that non-neuronal cells could be reprogrammed into neurons or neuroblasts in vivo (Buffo et al, 2005;Ohori et al, 2006;Grande et al, 2013;Niu et al, 2013;Torper et al, 2013;Guo et al, 2014;Su et al, 2014). However, it remains poorly understood how astrocyte-to-neuron conversion occurs in vivo and whether these induced neuronal (iN) cells could be incorporated into the preexisting neural circuits (Arlotta and Berninger, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For examples, postnatal astrocytes of the mouse cerebral cortex can be converted into glutamatergic and GABAergic neurons after overexpression of the transcription factors Neurog2 and Dlx2, respectively (Berninger et al, 2007b;. Several studies further showed that non-neuronal cells could be reprogrammed into neurons or neuroblasts in vivo (Buffo et al, 2005;Ohori et al, 2006;Grande et al, 2013;Niu et al, 2013;Torper et al, 2013;Guo et al, 2014;Su et al, 2014). However, it remains poorly understood how astrocyte-to-neuron conversion occurs in vivo and whether these induced neuronal (iN) cells could be incorporated into the preexisting neural circuits (Arlotta and Berninger, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that non-neuronal cells can be reprogrammed into neurons in the adult injured cortex, striatum, and spinal cord that were induced by stab wound or needle injection (Buffo et al, 2005;Grande et al, 2013;Guo et al, 2014;Su et al, 2014). In most of our above experiments involving stereotactic injection of AAV virus, we used injection micropipettes with diameters of 18 -20 m, and cells away from the injection sites were analyzed (Fig.…”
Section: In Vivo Conversion Of Dorsal Midbrain Astrocytes From Adult mentioning
confidence: 99%
“…Il est donc tout à fait envisageable que les cellules reprogrammées aient eu pour origine des astrocytes réactionnels plutôt que quiescents. C'est en utilisant une approche chirurgicale identique que l'équipe de Mataso Nakafuku rapporte l'obtention de néo-neurones dans un cerveau cette fois décrit comme lésé, en réponse au facteur de transcription Neurog2 et à l'addition des facteurs de croissance FGF2 (fibrobalst growth factor) et EGF (epithelial growth factor) dans le cortex et le striatum [40]. Si les auteurs n'ont pas identifié l'origine cellulaire des candidats à la reprogrammation, l'hypothèse des glies réactionnelles vient immédiatement à l'esprit.…”
Section: Les Glies Candidats Favoris à La Reprogrammation Neuronaleunclassified
“…Si les auteurs n'ont pas identifié l'origine cellulaire des candidats à la reprogrammation, l'hypothèse des glies réactionnelles vient immédiatement à l'esprit. De manière intéres-sante, ils observent que la reprogrammation est plus efficace dans le striatum que dans le cortex, et que l'identité des neurones générés varie en fonction de la structure ciblée : GABAergique dans le striatum, glutamatergique dans le cortex [40] ( Figure 1A). Ceci révèle à nouveau l'influence de l'environnement sur la production et la spécification des …”
Section: Les Glies Candidats Favoris à La Reprogrammation Neuronaleunclassified
See 1 more Smart Citation